“You might judge me!”: parents’ mobile device use with young children with SEND at home - Saracoglu, Yunus (2025)
Background: Previous research has shown that young children’s ownership and use of mobile devices (smartphones and tablets) at home is growing globally. This has led many researchers to examine the possible effects of these devices on the development of young children. A growing body of research has explored screen device use of typically developing children and their parents’ attitudes and practices towards this, and a few studies have focused on children with autism spectrum disorder (ASD). However, it is still unexplored how young children with special educational needs and disabilities (SEND, e.g., children with Down’s syndrome, children with learning disability) are using mobile devices at home and parents’ attitudes and practices regarding this use. This study examined mobile device use by young children with SEND (under 7 years) at home and parents’ perspectives and practices regarding mobile device use in the United Kingdom (UK). Methods: This study adopted the explanatory sequential research design, a mixed-method research approach, which consisted of two stages. In the first stage, 39 parents of young children with SEND completed an online survey on their children’s mobile device use at home and their attitudes and practices on this use. In the second stage, 9 semi-structured online interviews were conducted with parents who completed the survey in the first stage and were interested in attending a follow-up interview via Microsoft Teams. While the participants of the survey were more diverse in terms of their children’s conditions, interviews were conducted with parents of children with Down’s syndrome (n=6) and with Autism (n=3). The quantitative data collected from the surveys were analysed using descriptive statistics, and qualitative data gathered from the interviews were analysed using thematic analysis. In the present study, Cultural-historical Activity Theory (CHAT) was adopted as a theoretical framework that provided rich insights into the data analysis by highlighting the key role of the broader context in affecting parents’ attitudes and practices regarding mobile device use with their children. Results: The survey results showed that almost 82% of children with SEND were using a mobile device at home. Specifically, 71.8% of responders reported that their children with SEND were using a tablet, and 48.7% reported smartphone use at home. Overall, parents had an overwhelmingly positive view of their child’s mobile device use. 71.7 % of parents agreed that the use of mobile devices is beneficial for early learning and development. Nevertheless, 61.5% of surveyed parents thought that the overuse of mobile devices has a negative effect on children’s social interaction. Almost all of the interviewees acknowledged that the overuse of mobile devices may have negative effects on their children and that parents should limit their children’s mobile device use. Parents adopted some mediation strategies to prevent the negative effects of screen use on their children, such as setting time limits, co-use of devices, and monitoring children’s device use. The qualitative results showed that parents use mobile devices with their children for various purposes, including parenting (babysitting), entertainment, and education. Participants highlighted the educational benefits of mobile device use, and they use mobile devices with their children to facilitate language and speech development; teach Makaton signs; support early literacy development; and support numeracy development. Conclusion: Mobile device use was high among young children with SEND with tablets being the most common mobile device used at home. Parents had mixed feelings, neither totally positive nor negative, about the use of mobile devices by young children with SEND. Furthermore, it seems that young children's parents tend to use mobile devices as an instrumental tool in their childrearing practices, which has been considered part of 21st-century parenting in the literature. Although there were some similarities between parents of children with SEND and parents without SEND regarding their mobile device use with their child, there were some attitudes and practices that were unique to parents of young children with SEND. In line with CHAT, the findings of the present study showed that parents' (subject) mobile device use with their young children with SEND is shaped by the availability of mobile devices (tool), parents’ motivations/intentions (object: Educational, entertainment, babysitting), rules (e.g., approved apps and content, time limit), community (home environment, charities, media, schools), division of the labour (children with SEND, educators, health practitioners).